Ambrosiaster's commentary on the Pauline Epistles:Romans - Ambrosiaster (Writings from the Greco-Roman world, 2017)
The ancient writer dubbed Ambrosiaster was a pioneer in the revival of interest in the Pauline Epistles in the fourth century. He was read by later Latin writers, including Pelagius and Augustine, and his writings, passed on pseudonymously, had a long afterlife in the biblical commentaries, theological treatises, and canonical literature of the medieval and the early modern periods. In addition to his importance as an interpreter of scripture, Ambrosiaster provides unique perspectives on many facets of Christian life in Rome, from the emergence of clerical celibacy to the development of liturgical practices to the subordination of women. His commentary on the Pauline Epistles will be of interest to students of biblical interpretation and ancient Christianity.